1989
DOI: 10.1002/ajmg.1320320404
|View full text |Cite
|
Sign up to set email alerts
|

Polyasplenia complex with mesocardia and renal agenesis in an infant of a diabetic mother

Abstract: Despite improved prenatal care, infants of diabetic mothers (IDM) have an increased risk of congenital malformations. We report on an IDM with multiple congenital anomalies consistent with the polyasplenia complex with associated mesocardia and renal agenesis. The morphologic characteristics of these malformations are discussed. Special emphasis is given to the polyasplenia complex as an example of midline developmental field defect. The importance of maternal levels of hemoglobin A1c in relation to congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Thus, these aspects are in agreement with the results of the present study that strongly suggest that maternal diabetes mellitus (which acts during blastogenesis) is related to heterotaxia, particularly transposition of great vessels and transposition of viscera. This is also in agreement with the results of Becerra et al [1990], the experimental study of Morishima et al [1996], and the previous clinical observations [Gonzalez et al, 1989; Carey et al, 1991; Slavotinek et al, 1996; Lin et al, 1998; Guerritsen et al, 1999; Splitt et al, 1999; J.M. Graham, personal communication].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, these aspects are in agreement with the results of the present study that strongly suggest that maternal diabetes mellitus (which acts during blastogenesis) is related to heterotaxia, particularly transposition of great vessels and transposition of viscera. This is also in agreement with the results of Becerra et al [1990], the experimental study of Morishima et al [1996], and the previous clinical observations [Gonzalez et al, 1989; Carey et al, 1991; Slavotinek et al, 1996; Lin et al, 1998; Guerritsen et al, 1999; Splitt et al, 1999; J.M. Graham, personal communication].…”
Section: Discussionsupporting
confidence: 91%
“…There are previous publications focused on the possible relationship between maternal diabetes and malformed infants presenting heterotaxia‐asymmetry defects [Gonzalez et al, 1989; Slavotinek et al, 1996; Lin et al, 1998; Splitt et al, 1999]. Up to eight other malformed infants of mothers with diabetes mellitus, who also had heterotaxia‐asymmetry problems, have been described [Carey et al, 1991; Guerritsen et al, 1999; JM Graham, personal communication], and these authors concluded that heterotaxia should be considered as diabetic‐related malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Infants born to diabetic mothers have a three‐ to sixfold higher rate of malformation than infants born to nondiabetic mothers [Kučera, 1971; Pederson et al, 1964]. Caudal dysgenesis is classically linked to maternal diabetes [Williamson, 1970], but many other types of anomalies including congenital heart defects, renal anomalies, and neural tube defects are described frequently [Gonzalez et al, 1989; Khoury et al, 1989; Novak and Robinson, 1994; Robin et al, 1996; Tyral, 1996]. However, craniofacial anomalies have been described in only a small number of reports [Becerra et al, 1990; Johnson et al, 1983; Ramos‐Arroyo et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…An association of aural, cardiac, vertebral, and C.N.S. malformations in 5 IDMs was reported by Grix et al [19821. Recently, 3 more associations were described in infants of mothers with diabetes mellitus: VACTERL, midline defects, and prelpostaxial acrofacial dysostosis [Khoury et al, 1989;Gonzalez et al, 1989;RichieriCosta and Guion-Almeida, 19891.…”
Section: Discussionmentioning
confidence: 99%